2019
DOI: 10.1186/s13041-019-0512-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral analysis in mice deficient for GAREM2 (Grb2-associated regulator of Erk/MAPK subtype2) that is a subtype of highly expressing in the brain

Abstract: Grb2-associated regulator of Erk/MAPK (GAREM), is an adaptor protein related to the several cell growth factor receptor-signaling. The GAREM family has two subtypes, GAREM1 and GAREM2, both encoded in the human and mouse genome. Recent genome-wide research identified GAREM2 as a candidate of neurodegenerative diseases. Here, we use knockout (KO) mice to show the role of GAREM2, that is highly expressed in the brain. According to the comprehensive behavioral battery, they exhibited less anxiety both in elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Additionally, it is interesting to explore whether corticosterone levels reflect “anxiety” levels that are naturally induced by exposure to potentially aversive situations in the elevated plus maze in C57BL/6J mice. In the present study, to examine the influences of experience with a battery of behavioral tests that did not include the elevated plus maze test on subsequent elevated plus maze behavior and plasma corticosterone responses in male C57BL/6J mice, animals were first subjected to a behavioral test battery, including an assessment of general health and neurological reflexes, a light/dark transition test, and an open field test, which have been extensively used to characterize the behavioral phenotypes of many strains of mutant and inbred mice in our laboratory [e.g., 40 43 ] and in other laboratories [e.g., 44 47 ]. Mice with and without experience with the behavioral test battery were tested in the elevated plus maze, and immediately after exposure to the maze, their blood was collected to measure plasma corticosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is interesting to explore whether corticosterone levels reflect “anxiety” levels that are naturally induced by exposure to potentially aversive situations in the elevated plus maze in C57BL/6J mice. In the present study, to examine the influences of experience with a battery of behavioral tests that did not include the elevated plus maze test on subsequent elevated plus maze behavior and plasma corticosterone responses in male C57BL/6J mice, animals were first subjected to a behavioral test battery, including an assessment of general health and neurological reflexes, a light/dark transition test, and an open field test, which have been extensively used to characterize the behavioral phenotypes of many strains of mutant and inbred mice in our laboratory [e.g., 40 43 ] and in other laboratories [e.g., 44 47 ]. Mice with and without experience with the behavioral test battery were tested in the elevated plus maze, and immediately after exposure to the maze, their blood was collected to measure plasma corticosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of a comprehensive behavioral battery, there were slight emotional differences between GAREM2 knockout and wild-type mice, and the knockout mice exhibited less anxiety, mildly increased social approach behavior, and longer latency to immobility. Additionally, neurite extension was suppressed in the primary culture of neurons derived from GAREM2 KO mice [10]. Studies using knockout animals have not revealed a relationship between GAREM2 function and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of GAREM2 knockout mice showed that while the loss of GAREM2 does not cause significant changes in brain function itself, these knockout mice exhibited emotional alterations, such as less anxiety, mildly increased social approaching behavior, and longer latency to immobility as compared to wild-type mice (WT) [10]. Furthermore, neurite outgrowth in primary cultured neurons was suppressed in neurons derived from GAREM2 knockout mice.…”
mentioning
confidence: 99%
“…The test was conducted for 10 min. 29 The immobility time, which is indicative of helpless behavior, was recorded. 30 …”
Section: Methodsmentioning
confidence: 99%
“…The test was conducted for 10 min. 29 The immobility time, which is indicative of helpless behavior, was recorded. 30 In the forced swim test (FST), the mice swam in an open glass beaker (height 18.5 cm and diameter 14.5 cm) filled with water (23-25 °C) up to a height of 12 cm to prevent the mice from supporting themselves against the bottom of the beaker.…”
Section: Behavioral Testsmentioning
confidence: 99%